WORKSHOP ECO PRINT PADA MEDIA TOTE BAG DI KECAMATAN PULO GADUNG - Viana Prasetio; Cut Erra Rismorlita; Frida Philiyanti; Callia Rahmadhila; Chika Amalia; Dyan Wulandari; Fadhilah Zahra Maulana; Fadira Trisnayola; Fadian Ahyar Raudhan; Fauzi Asa Walidaini; Regitha Dwi Qinthana; Seffina Fitriandi; Sekar Rismalia Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This community service program was conducted in Pulo Gadung district, focusing on a workshop titled